Antioxidant Activity and Tyrosinase Inhibitor of Red Betel Leaf Extract - Mustika Weni; Mega Safithri (Indonesian Journal of Applied Research (IJAR), 2023)
Red betel leaf (Piper Crocatum) contains flavonoids, tannins, steroids, and alkaloids, known to act as antioxidants. This study aimed to determine the antioxidant activity of red betel leaf extract. The solvents used for the extraction process are ethanol and n-hexane. The thiobarbituric acid (TBA) method was used to determine antioxidant activity. The results showed that the extract of 200 ppm inhibited fatty acid oxidation by 52.13%. No significant difference (α = 0.05) inhibition of unsaturated fatty acids oxidation between the sample and α-tocopherol at 200 ppm. The ethanol extract of red betel can inhibit the tyrosinase enzyme higher than the n-hexane extract of red betel, as seen from the IC50 value of the ethanol extract of red betel of 1655 ppm, while the IC50 value of n-hexane of red betel is 3090.56 ppm.